1994
DOI: 10.1111/j.1365-2141.1994.tb05024.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐mRNA and Hb F levels in β‐thalassaemia

Abstract: The Hb F levels in beta-thalassaemia can be affected by factors both linked and unlinked to the beta-globin gene cluster. We have recently analysed a group of patients with a homozygosity for the IVS-I-6 (T-->C) mutation, showing a wide variation in Hb F levels (2-47%) which could not be accounted for by any sequence variation within regulatory elements of the beta-globin gene cluster. In order to further investigate factors underlying this phenotypic difference we have developed a competitive reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…38 The relative amounts of γ-and -mRNA were determined by RT-PCR methodology described in detail by Efremov 39 in thalassaemia major and -thal intermedia patients.…”
Section: Rna Analysismentioning
confidence: 99%
“…38 The relative amounts of γ-and -mRNA were determined by RT-PCR methodology described in detail by Efremov 39 in thalassaemia major and -thal intermedia patients.…”
Section: Rna Analysismentioning
confidence: 99%
“…These may be the mechanisms which normally contribute, in addition to decreased transcription, to the reduced expression of HbA 2 , namely decreased mRNA stability or decreased translational efficiency. The recent finding of higher ratios of γ-mRNA to HbF levels in peripheral blood erythroid cells from adults as compared to newborns suggests a corresponding mechanism for the control of HbF [17]. The known reciprocal control of the transcription of the γ- and β-globin genes [18, 19]through competitive interactions with the locus control regions may contribute to an increased transcription of the other β-like genes (δ or γ) when the β-globin gene transcription is repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Deter mination of the a2/al, the a/p, and the y/p ratios is based on RT-PCR methodology described in detail by Efremov et al [9,10], by Molchanova et al [14], and by Smetanina et al [15]. …”
Section: Methodsmentioning
confidence: 99%
“…As a result, both (3°-or (P-thal occur. In (3+-thal, P-chain synthesis remains but at a markedly reduced rate and there is a cor respondingly reduced level of P-globin messenger RNA (mRNA) in reticulocytes [3,4], No P-chains are synthe sized in P°-thal, and early studies of the globin mRNA in this condition demonstrated a heterogeneity at the molec ular level [5][6][7][8], Recent development of methodology involving a re verse transcriptase-polymerase chain reaction (RT-PCR) procedure provides a useful and sensitive technique for the study of gene expression [9][10][11][12][13][14] because this RT-PCR method makes it simple to analyze the relative quantities of the globin mRNAs in human reticulocytes. We have used this method to quantitate the relative levels of a-and P-globin mRNA in a-thal patients [15].…”
mentioning
confidence: 99%